2021
DOI: 10.1108/ijbm-11-2020-0551
|View full text |Cite
|
Sign up to set email alerts
|

Mobile investment technology adoption among investors

Abstract: PurposeThe purpose of this study is to examine investors' internal characteristics, including investment literacy, risk tolerance and familiarity with mobile financial services, as antecedents of mobile investment technology adoption among American investors.Design/methodology/approachUsing the 2018 National Financial Capability Study and its supplemental Investor Survey, this study examined antecedents, including investors' internal characteristics, in relation to mobile investment technology adoption. Nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…, 2019; Seiler and Fanenbruck, 2021; Wang et al. , 2021; Fan, 2021). We add to this literature by showing that even if an individual was to adopt an AI-enabled system (robo-advisor), their intention to invest may be inhibited because they did not receive the information from a human advisor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2019; Seiler and Fanenbruck, 2021; Wang et al. , 2021; Fan, 2021). We add to this literature by showing that even if an individual was to adopt an AI-enabled system (robo-advisor), their intention to invest may be inhibited because they did not receive the information from a human advisor.…”
Section: Discussionmentioning
confidence: 99%
“…First, we tested a novel prediction that financial information provided by a robo-advisor (rather than a human) would result in less willingness to invest. This is significant because most research has previously focussed on the antecedents of adoption (Zhang et al, 2021;Belanche et al, 2019;Seiler and Fanenbruck, 2021;Wang et al, 2021;Fan, 2021). We add to this literature by showing that even if an individual was to adopt an AI-enabled system (robo-advisor), their intention to invest may be inhibited because they did not receive the information from a human advisor.…”
Section: Theoretical Contributionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, research suggests that users' trust that smartphones meet usage expectations, and their familiarity with smartphones, will positively influence the continued use of technology (Idemudia and Raisinghani 2014). A recent study noted that users' experience with mobile payments and transfers were significant factors that influenced their adoption of mobile investment technologies (Fan 2021). Thus, individuals not accustomed to digital technologies such as the internet or mobile phones for payment, purchase, or cash transactions may not be interested in adopting innovative services such as FinTechs.…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic differences in financial technology adoption Previous studies have documented a difference in general use behaviors related to innovative technology by race and ethnicity. Several studies have reported that compared to Caucasian/ Whites, racial/ethnic minorities have adopted mobile banking to a greater extent (Blanco et al, 2017;Federal Deposit Insurance Corporation, 2020;Federal Reserve Board, 2016), rely on mobile investment recommendations, make investments using a mobile device (Fan, 2022) and use personal financial management (PFM) technology (Walsh and Lim, 2020). However, the percentage of online banking users was higher among Whites (26.7%) compared to Blacks (12%), Hispanics (11.1%), Asians (25.7%) and Native Americans/Alaska Natives (17%) in 2019 (Federal Deposit Insurance Corporation, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%